Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.26582/k.50.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the talk test and percent heart rate reserve for exercise prescription

Abstract: Exercise intensity is traditionally prescribed using %HRmax, %HRR, %VO2max, or %VO2R. Recently, the Talk Test (TT) has been proposed as an alternative method to guide exercise intensity. However, it is unknown if prescribing exercise intensity solely using the TT can provoke training responses that are comparable to traditional guidelines. This study compared the responses to training using either the TT or %HRR. Forty-four subjects (17 males and 27 females: age=20.4±3.02 years; body height=170.5±9.79 cm; body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The talk test is based on the concept used by mountain climbers in 1937 26 . The utility of the talk test, as a tool for exercise prescription, has been established in sedentary26, 27, 28, 29, 30, 31, 32 and trained33, 34 healthy young adults 35 . It has also been shown to be useful in Phase II and III CR of cardiac patients 36, 37, 38, 39, 40, 41, 42, 43.…”
Section: Talk Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The talk test is based on the concept used by mountain climbers in 1937 26 . The utility of the talk test, as a tool for exercise prescription, has been established in sedentary26, 27, 28, 29, 30, 31, 32 and trained33, 34 healthy young adults 35 . It has also been shown to be useful in Phase II and III CR of cardiac patients 36, 37, 38, 39, 40, 41, 42, 43.…”
Section: Talk Testmentioning
confidence: 99%
“…The participant's response from the talk test is well correlated with therapist observation in graded exercise test literature 37, 39, 40. The talk test has been used while walking/running on treadmill,28, 29, 30, 31, 32, 33, 34, 37, 41, 49 cycle ergometer,26, 27, 30, 31, 35, 36, 39, 40, 42 and track walking 41 . So, it can be easily administered in majority of day-to-day physical activities of cardiac patients.…”
Section: Talk Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The TT has been shown to be a valuable tool for guiding exercise training as well. Porcari et al (2018) showed that exercise capacity improved, when measured by both VO 2 max and PO (Watts), regardless of whether training was guided by the %HRR method or by the TT. Participants in the TT group tended to exercise between 70-75% HRR, which is within the recommended zone according to the ACSM guidelines (2017).…”
Section: Discussionmentioning
confidence: 95%
“…The dominant model for subsequent exercise prescription is based on a percentage of the maximal exercise capacity (metabolic equivalents (METs)), heart rate (HR) or HR reserve (%HRR) [21], rating of perceived exertion (RPE) [22], or ventilatory threshold (VT) [23]. Recently, the talk test, which can be taken as a surrogate of VT, has been effectively used to prescribe exercise training [24,25] and to avoid ischemia during training [26].…”
Section: Introductionmentioning
confidence: 99%